Lactarius indoevosmus and L. kanadii (Russulaceae), two new species from the northwestern Himalayas, India, inferred from morphology and molecular data - Verma, Komal; Mehmood, Tahir; Uniyal, Priyanka; Sharma, Yash Pal (Phytotaxa, 2022)
Two new species of the genus Lactarius from India, Lactarius indoevosmus (L. subg. Lactarius) and L. kanadii (L. subg. Plinthogalus) are presented with detailed descriptions, line drawings, photomicrographs, and comparisons with related species. The novelty and placement of these taxa within the genus Lactarius are confirmed with an ITS-based phylogeny.